Abyad’s Theatrical Personality in the 20th-Century Egyptian Theater - Turgay Gökgöz (Şarkiyat Mecmuası)
Modern Arab theater was born in Lebanon, but due to circumstances, it had the opportunity to develop in Egypt and could be moved until today thanks to important personalities. In Egypt, where the art of theater met for the first time with the Nahda Movement, which started with the invasion of Egypt by Napoleon in 1798, the art of theater later underwent serious development with Ya‘qûb Sannû‘ Egyptian Jew. In this context, George Abyad, a Lebanese immigrant to Egypt, visited North African countries such as Algeria and Tunisia with his troupe to spread the art of theater. In fact, before George Abyad, it was Ya‘qûb Sannû‘ who had laid the foundation of Egyptian theater. It would be appropriate to say that the seeds of theater art were sown in Arab countries thanks to these troupes. George Abyad was a name that brought the musical to Egyptian theater, brought artistic theater to Egypt, and standardized drama. George Abyad has an important place in the history of Arab theater in terms of staging classical and historical plays as well as French plays, contributing to Egyptian Arab theater as a Lebanese theater, and setting an example for the new generation of theater artists. In this article, it aims to provide broad information about the Lebanese theater actor George Abyad and his theater personality, which we have not come across in our country.